Analysis Of Information System Acceptance And Puskesmas Management (Simpus) In Tasikmadu Karanganyar Puskesmas - Prianggi, Herawati; Ario Kresno; Prawisty Agnes (Journal for Quality in Public Health, 2024)
Technological developments in Indonesia require the government to move quickly to implement a fast, accurate and up-to-date information system in the health sector. In implementing this information system, the government created an information system (SIMPUS). The national e-health strategy is a comprehensive approach to planning, developing, implementing and evaluating the use of information and communication technology in the health sector nationally, which is becoming a trend in global health services, namely electronic health records. Information systems at community health centers have been developed to overcome problems such as data input, as a primary data source for managing health statistical data. Simpus is an application program or computer software created with the aim of supporting community health center management in providing services quickly and easily to patients. Optimal use of SIMPUS can reduce workload and increase the efficiency of registration services to patients. This study aims to analyze the characteristics of the SIMPUS sample at the Tasikmadu Karanganyar Community Health Center. Research Method is a Observational research with a cross-sectional study design was conducted in Tasikmadu. Results Shows that the largest profession is nurse /midwife /laboratory /pharmacist /healthanalysis /physiotherapy with 28 (50.00%) people, while the smallest profession is general practitioner/functional/dentist with 5 (12.50%).